SCHOOL STRATEGY TO BUILD STUDENTS' SOCIAL SOLIDARITY DURING ONLINE LEARNING - Suwidiyanti Suwidiyanti; Isa Anshori (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
Teaching and learning in the school aim to enable students to gain knowledge and change behavior. Therefore, schools need to instil the values of social solidarity to respond to differences in society. Emile Durkheim's theories form the basis of the analysis of social facts about social solidarity. This study aims to describe the school's strategic steps in building social solidarity among students during online learning due to the impact of COVID-19 at SMA Muhammadiyah 2 Sidoarjo. This research uses a qualitative approach to the type of case study. Data collection was taken through interviews and documentation. The data were analyzed using the Miles and Huberman model with data collection, data reduction, data display, and conclusion/verification. The technique of data validity by triangulation. The results showed that strategic steps in building the social solidarity of students during online learning include: (1) The school uses Moodle application to support online learning, which can control the teacher's learning activities; (2) The principal determines by instructing all teachers to a) Each learning hour uses virtual face-to-face using zoom or google meet followed by Moodle application, b) Creating integrated learning tools in forming social solidarity values, c) Using learning methods and models that emphasize group learning; and (3) Schools facilitate infaq online.